Infants' object processing is guided specifically by social cues - Michel, Christine; Pauen, Sabina; Höhl, Stefanie (Neuropsychologia, 2019)
Previous studies showed that the movements of another person's eyes and head guides infants' attention and promotes social learning by leading to enhanced encoding of cued objects. However, it is an open question whether social features like eyes are required or if the lateral movement of any arbitrary stimulus can elicit similar effects. The current experiments investigate the effects of the movement of a nonsocial cue and a perceptually similar social cue on object processing in 4-month-olds using event-related potentials (ERPs). Infants were presented with one of two central cues, either a box with a checkerboard pattern or a box with eye-like features on the front, which turned to one side. The cue thereby either turned toward a novel object or turned away from it. Afterwards, the object was presented again and ERPs in response to these previously cued or uncued objects were compared. When the nonsocial box served as the cue, no difference in neural processing of previously cued and uncued objects was found. In contrast, when the box with eyes served as the cue, we found an enhanced positive slow wave (PSW) for uncued as compared to cued objects. While the turning of the box with eyes promoted the encoding of cued objects, uncued objects needed enhanced activity for processing when presented for a second time. Results suggest that not every dynamic cue can influence infants' object processing but that the presence of a basic social characteristic like isolated schematic eyes is sufficient to enhance social learning processes in early infancy. This hints on a specific sensitivity of the infant brain to social information which helps infants to focus on relevant information in the environment during social learning.